Factors influencing customer purchase intention towards halal logo on food packaging in Melaka - Siti Hajar Binti Mohtar; Mohd Syaiful Rizal; Mohamad Toha; Anastasia Lidya Maukar (President University, 2021)
This research aims to examine the factors influencing Melaka Muslim community in purchase intention towards halal logo on food packaging. Theory of Planned Behaviour is used as theoretical framework and there are three factors in influencing customer purchase intention which are attitude, subjective norm and perceived behavioural control. Questionnaires were distributed to the 170 Muslims respondent which randomly selected in shopping complex or supermarket area in Melaka City. The data was analysed using statistical package, descriptive analysis, Pearson correlation and multiple regression analysis were applied in this research in order to identify relationship and the most important factors. The results indicated that attitude, subjective norm and perceived behavioural control have positive relationship to intention on purchasing food packaging with halal logo. The most important factor that influence consumer purchase intention towards halal logo was attitude and subjective norm.